Bensonetal.CanisHybridZoneBodyLengthData - Benson, John F.; Patterson, Brent R.; Wheeldon, Tyler J. (Dryad Digital Repository, 2012)
Body length data for captured wolves, coyotes, hybrids. BL = body length in cm. EW = eastern wolf, gray = gray wolf.